REKAYASA KEPEMIMPINAN DALAM BIROKRASI: SUATU PARADIGMA MEMBENTUK PERILAKU BIROKRASI - Riyadi, Riyadi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
The common negative phenomenon among leaders within bureaucratic context is usually in the form of the lack of understanding of the organization?s goals. The leaders tend to get bogged down on routine activities; as a result, they are unable to develop an innovative model for their jobs. Patrimonialism and patron-client culture have become fossilized among bureaucratic leaders. In addition, like and dislike still plays a role in the personnel promotion process. Feudalistic, otoriarian, and undemocratic leadership definitely influences the bureaucratic behaviours. To overcome those problems, a measure to improve leadership quality needs to be taken in the form of leadership engineering based upon the model of professional work cultures. Deploying this model is expected to be able to convert bureaucratic mindset towards reward system rather than just punishment one. In other words, the ability to construct a more humanistic relation for both internal and external circumstances, is the key factor to sucessful leadership as well as the ability tomotivate their teams.